Assertive Speech Strategy between Russian and Ukrainian Ambassadors Regarding the Topic of the Russia-Ukraine Conflict: A Cross-Cultural Pragmatics Study - Izdihar, Hana’; Rizal Agung Kurnia (BRIN Publishing (Penerbit BRIN), 2025)
Cross-cultural pragmatics highlights how utterances convey meaning across different cultural contexts, yet studies integrating assertive speech acts within this framework remain limited. This study investigates the assertive speech strategies of the Russian and Ukrainian Ambassadors to Indonesia in a BBC News Indonesia interview concerning the Russia–Ukraine conflict. Employing a descriptive qualitative design, the data were drawn from interview transcripts, identified through note-taking, and analyzed inductively based on speech act theory and cross-cultural pragmatics. The findings show clear differences in the functions of assertive speech acts between the two ambassadors. The Russian Ambassador predominantly employed statements to express his country’s perspective and to defend Russia’s position, while the Ukrainian Ambassador, representing the victimized side, relied more on affirmations to emphasize Russia’s aggression. Despite the absence of explicit lexical markers, functional patterns of assertive utterances were identified from the speech context. This study contributes by filling a gap in research on assertive speech within cross-cultural pragmatics and provides insights into how cultural and political backgrounds shape diplomatic discourse.